NURSE PHYSICIAN COMMUNICATION IN THE PERIOPERATIVE ENVIRONMENT: DISCOURSE AND ACTIONS TO TRANSFORM HEALTH CARE - Weeks, Marlene (Operating Room Nurses Association of Canada Journal, 2005)
In a previous article by Weeks1, discourse regarding nurse physician communication within acute care settings is presented and analyzed following the principles of critical discourse analysis (CDA)2. An understanding of what shapes nurse physician communication discourse and its role in the reproduction of the dominance of nurses by physicians is gained in this previous article. This understanding allows for further exploration of the role of discourse in the challenge of that dominance leading to suggested actions to transform health care delivery, which is the focus in this article.